Aspekty monokulturowe pomocowej choroby holenderskiej - Jasiński, Michał (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article considers theoretical threats of Dutch disease caused by offcial development aid (ODA), particularly its extreme stage called “aid monoculture”. The study presented in the article is an introduction to further research devoted to a wider issue of effectiveness of ODA.